Optimalisasi kesejahteraan psikologis lansia Desa Sempulur melalui psikoedukasi berbasis refleksi diri dan interaksi sosial - Nailah Rizkiyanti Salma; Azka Fauziah; Khoiril Anam; Sugiarto Sugiarto (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2026)
The increasing elderly population demands serious attention to psychological well-being, particularly in communities with limited social support. Observations in Sempulur Village indicate that many elderly people live alone, have limited social activities, and receive minimal psychological stimulation. This community service program aims to improve the psychological well-being of elderly people through a psychoeducational program based on self-reflection and social interaction. The implementation method involves several stages: needs analysis, program design, activity implementation, and evaluation. The program is implemented through participatory group activities that include healthy elderly exercise, reflection on life experiences (reminiscence), and art therapy to stimulate aspects of self- acceptance, autonomy, and purpose in life. A total of 15 elderly people (1 man and 14 women) participated in a series of programs that were evaluated through a psychological well-being survey and participatory observation. Results showed increased social participation, active involvement in group activities, and increased self-expression and a sense of meaning in life. Furthermore, this program also had a positive impact by providing a forum for psychosocial activities that can be utilized sustainably by the village community. Thus, this program contributes to improving the psychological well-being of elderly people in a community-based manner.